2021
DOI: 10.2106/jbjs.20.01178
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Minimally Invasive Chevron and Akin Osteotomies (MICA) in Hallux Valgus Surgery

Abstract: Background: There is interest in hallux valgus deformity correction using internal fixation with the minimally invasive chevron and Akin osteotomies (MICA) technique. The objective of this study was to assess the correction measured on postoperative radiographs and clinical outcomes, using validated outcome measures, at 2 years following third-generation MICA. Methods: This is a prospective single-surgeon case series of 333 consecutive feet that underwent MICA surgery betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 43 publications
5
70
2
Order By: Relevance
“…One potential disadvantage of this technique is the decreased stability of the metatarsal osteotomy fixation with only 1 dorsal screw. 13 Recent literature supports the use of the increasingly popular MICA technique as described by Redfern et al, 23-25,42 and our study provides a timely comparison of this technique against the well-established scarf-Akin osteotomy.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…One potential disadvantage of this technique is the decreased stability of the metatarsal osteotomy fixation with only 1 dorsal screw. 13 Recent literature supports the use of the increasingly popular MICA technique as described by Redfern et al, 23-25,42 and our study provides a timely comparison of this technique against the well-established scarf-Akin osteotomy.…”
Section: Discussionsupporting
confidence: 59%
“…In a series of 40 MICA cases, Holme et al 17 reported improvement in AOFAS scores from 48 to 93, HVA from 32 to 12 degrees, and IMA from 13 to 7 degrees. More recently, in a larger series of 292 MICA cases, Lewis et al 24 reported improvement in each domain of the Manchester-Oxford Foot Questionnaire (MOXFQ) score; HVA also improved from 32.9 to 8.7 degrees, and IMA improved from 15.3 to 5.7 degrees. However, the available literature on the MICA technique is still limited and developing, especially compared with the widely established scarf-Akin osteotomy procedure that has long-term data of up to 10 years reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is evidence that females younger than 65 years with HV had a statistically significantly worse quality of life than females of the same age group in the general population [26], and that HV surgery resulted in decreased body pain and improved physical function and patient quality of life [27]. More than 100 different procedures for treating hallux valgus have been described [28]; they include combinations of soft tissue balancing, bone osteotomies and joint fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Two large case series showed the results of minimally invasive chevron and Akin osteotomies for hallux valgus correction. At a minimum follow-up of 2 years, Lewis et al 16 noted significant improvement in all radiographic parameters, VAS pain scores, and all domains of the Manchester-Oxford Foot Questionnaire in 292 cases. There were 3 recurrences (0.9%).…”
Section: Forefootmentioning
confidence: 98%